A household perspective on access to health care in the context of HIV and disability: a qualitative case study from Malawi. Issue 1 (December 2016) - Braathen, Stine; Sanudi, Lifah; Swartz, Leslie; Jürgens, Thomas; Banda, Hastings; Eide, Arne
Abstract Background Equitable access to health care is a challenge in many low-income countries. The most vulnerable segments of any population face increased challenges, as their vulnerability amplifies problems of the general population. This implies a heavy burden on informal care-givers in their immediate and extended households. However, research falls short of explaining the particular challenges experienced by these individuals and households. To build an evidence base from the ground, we present a single case study to explore and understand the individual experience, to honour what is distinctive about the story, but also to use the individual story to raise questions about the larger context. Methods We use a single qualitative case study approach to provide an in-depth, contextual and household perspective on barriers, facilitators, and consequences of care provided to persons with disability and HIV. Results The results from this study emphasise the burden that caring for an HIV positive and disabled family member places on an already impoverished household, and the need for support, not just for the HIV positive and disabled person, but for the entire household. Conclusions Disability and HIV do not only affect the individual, but the whole household, immediate and extended. It is crucial to consider the interconnectedness of the challenges faced by an individual and a household. Issues of health (physical and mental), disability, employment, education, infrastructure (transport/terrain) and poverty are all related and interconnected, and should be addressed as a whole in order to secure equity in health.